Integrated Multi‐Cohort Analysis of the Parkinson's Disease Gut Metagenome - Boktor, Joseph C.; Sharon, Gil; Verhagen Metman, Leo A.; Hall, Deborah A.; Engen, Phillip A.; Zreloff, Zoe; Hakim, Daniel J.; Bostick, John W.; Ousey, James; Lange, Danielle; Humphrey, Gregory; Ackermann, Gail; et al. (Movement disorders, 2023)
Background The gut microbiome is altered in several neurologic disorders, including Parkinson's disease (PD). Objectives The aim is to profile the fecal gut metagenome in PD for alterations in microbial composition, taxon abundance, metabolic pathways, and microbial gene products, and their relationship with disease progression. Methods Shotgun metagenomic sequencing was conducted on 244 stool donors from two independent cohorts in the United States, including individuals with PD (n = 48, n = 47, respectively), environmental household controls (HC, n = 29, n = 30), and community population controls (PC, n = 41, n = 49). Microbial features consistently altered in PD compared to HC and PC subjects were identified. Data were cross‐referenced to public metagenomic data sets from two previous studies in Germany and China to determine generalizable microbiome features. Results We find several significantly altered taxa between PD and controls within the two cohorts sequenced in this study. Analysis across global cohorts returns consistent changes only in Intestinimonas butyriciproducens. Pathway enrichment analysis reveals disruptions in microbial carbohydrate and lipid metabolism and increased amino acid and nucleotide metabolism in PD. Global gene‐level signatures indicate an increased response to oxidative stress, decreased cellular growth and microbial motility, and disrupted intercommunity signaling. Conclusions A metagenomic meta‐analysis of PD shows consistent and novel alterations in functional metabolic potential and microbial gene abundance across four independent studies from three continents. These data reveal that stereotypic changes in the functional potential of the gut microbiome are a consistent feature of PD, highlighting potential diagnostic and therapeutic avenues for future research. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.